Efficiency and Effectiveness Review of the National Housing Authority (NHA) Resettlement Program - Marife M. Ballesteros; Jasmine V. Egana (Philippine Institute for Development Studies (PIDS), 2013)
This paper examines the effectiveness and efficiency of implementation of the National Housing Authority (NHA) resettlement programs. The review focuses on the recent operations of NHA covering the period between 2003 and 2011, which covers one of the largest resettlement projects of NHA involving about 93,000 families for the North and South Rail infrastructure project. During this period, the resettlement program received about 85 percent of NHA budget. NHA has executed the development of 88 resettlement projects nationwide of which 45 project sites are located in Metro Manila and the peripheral areas (or the Greater Manila Area) and 43 in the regions. The dominant scheme in GMA is the Completed Housing Project (CHP) with more than 70 percent (32 sites) of total projects developer constructed. The balance consists of Incremental Housing Projects (IHP) (6 sites) and mixed projects (7 sites), which combined the CHP and IHP methods.By location, there are more in-city projects (68 sites) than off-city projects (20 sites). However, in-city projects are dominant only in the regions and provinces outside Metro Manila. In the highly urbanized cities of Metro Manila, large-scale resettlement was not provided due to land constraints. Based on actual cost per unit, it costs less to produce a unit of housing using the CHP scheme than IHP by about 17 percent or about PHP 25,000 per unit, on the average. However, cost benefit ratio analysis shows that IHP is more cost effective considering the value of developments and the greater participation and investments of households and community in maintenance of housing estates. Between in-city and off-city CHP projects, the average total project cost is higher for in-city projects compared to off-city projects mainly due to higher cost of land but in-city projects are more sustainable and acceptable to both households and local government units (LGUs).It is recommended that the most effective and efficient approach to resettlement is a combined approach of in-city and incremental housing. However, there are necessary conditions that require specific actions not only from NHA but other stakeholders as well to implement this approach such as: (1) land for socialized housing has to be made available by the LGU or national government especially in highly urbanized cities such as Metro Manila; (2) the feasibility of vertical developments in-city should be considered; and (3) the need for the NHA to improve the production process for incremental housing.
Keywords: 330; Philippines; resettlement programs; housing